2020
DOI: 10.1038/s41467-020-16497-x
|View full text |Cite|
|
Sign up to set email alerts
|

A hypomorphic cystathionine ß-synthase gene contributes to cavefish eye loss by disrupting optic vasculature

Abstract: Vestigial structures are key indicators of evolutionary descent, but the mechanisms underlying their development are poorly understood. This study examines vestigial eye formation in the teleost Astyanax mexicanus, which consists of a sighted surface-dwelling morph and multiple populations of blind cave morphs. Cavefish embryos initially develop eyes, but they subsequently degenerate and become vestigial structures embedded in the head. The mutated genes involved in cavefish vestigial eye formation have not be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…These studies have shown that eye loss is an additive trait controlled by more than a dozen QTL scattered across the genome [20,21]. Thus far, cbsa, which affects eye growth by interfering with optic vasculature function, is the only mutated gene that has been positively identified under an eye QTL [22]. The loss of melanin pigmentation is caused by differentiation of fewer melanophores, reduced melanin synthesis, which leads to brown coloration in some cavefish populations (e.g., Tinaja), and the complete loss of melanin, which results in albinism in other cavefish populations (e.g., Pachón and Molino) [23].…”
Section: Genetic Architecture Of Trait Evolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies have shown that eye loss is an additive trait controlled by more than a dozen QTL scattered across the genome [20,21]. Thus far, cbsa, which affects eye growth by interfering with optic vasculature function, is the only mutated gene that has been positively identified under an eye QTL [22]. The loss of melanin pigmentation is caused by differentiation of fewer melanophores, reduced melanin synthesis, which leads to brown coloration in some cavefish populations (e.g., Tinaja), and the complete loss of melanin, which results in albinism in other cavefish populations (e.g., Pachón and Molino) [23].…”
Section: Genetic Architecture Of Trait Evolutionmentioning
confidence: 99%
“…Genetic complementation between CRISPR-Cas9 surface fish mutants and cavefish can be used to confirm the relationship of edited genes to the genes responsible for naturally evolved cavefish traits and to evaluate off-target effects [55]. Gene overexpression has been carried out by injection of synthetic mRNAs or a gene fusion construct containing the zebrafish temperature-inducible hsp70 promoter into eggs [16,22].…”
Section: Gene Manipulationsmentioning
confidence: 99%
See 3 more Smart Citations